PENGELOLAAN SUMBERDAYA AIR TERPADU BERBASIS GEOGRAPHIC INFORMATION SYSTEM (GIS) DI KABUPATEN MUSI RAWAS UTARA - Emiliawati, Anna (Universitas Bina Taruna Gorontalo, 2023)
North Musi Rawas Regency is a new district that has a wealth of natural resources, one of which is water resources. However, the use of water resources is not maximized and not properly inventoried, especially in disaster activities such as floods and forest fires. This is because the condition of the area is difficult to reach, making it difficult for local governments to map the situation and potential of water resources. The increasing development of science and technology requires local governments to have special data collection systems for natural disaster situations and water resources, especially those that can be accessed by the public. The aim of this research is to identify natural disaster situations and water resource potential based on field data taken and provide information regarding natural disaster data (floods and forest fires) and water resource potential that can be accessed by the government and the public. It is hoped that the results of this research will provide a general overview of information regarding natural disaster situations and water resource potential in North Musi Rawas Regency so that it can become a work reference and decision/policy making for the Government/relevant agencies in disaster emergency response preparedness efforts and the development of sustainable water resource potential development. . The research location is North Musi Rawas Regency. The research method is a field survey. The survey carried out was to collect data and coordinate points for floods and forest fires as well as potential water resources. Next, hydrological system identification and data inventory will be carried out. Then the data was analyzed using a GIS application. The map contains information on disaster point data (floods and forest fires), water facilities and infrastructure as well as water resource potential as part of public information.